Research on hot water chemical flooding technology in Bohai heavy oil field - Jian, Zhang; Dan, Liang; Wensheng, Zhou; Qichen, Zhang; Liqi, Wang; Zhijie, Wei (Frontiers in Energy Research, 2024)
Introduction: The hot water chemical flooding technology effectively improves the fluidity ratio and enhances the horizontal and vertical oil displacement efficiency of the reservoir through the synergistic effect of thermal energy and chemicals, which can further enhance the recovery rate on the basis of throughput thermal recovery. Methods: Based on the geological reservoir parameters of Bohai B oilfield, an oil recovery system evaluation experiment and scheme design study were carried out. Injection parameters such as hot water temperature, chemical agent concentration, and chemical agent dosage that affect the oil recovery effect of hot water chemical flooding were optimized and designed. The development characteristics and effects of two thermal recovery technologies, namely multi thermal fluid throughput and hot water chemical flooding, were compared and analyzed. Results: The results show that with the increase of temperature, the effect of chemical agents on improving the water-oil mobility ratio and reducing the viscosity of crude oil is weakened, and the thermal energy plays a leading role in enhancing oil recovery, but when the temperature is higher than 115°C, the improvement of oil recovery is slowed down, and the comprehensive economic indicators decline rapidly. As the concentration of chemical agent increases, the enhanced oil recovery increases monotonously. When the concentration is 1500 mg/L, the comprehensive economic indicators reach the peak and then decline, indicating that the efficiency of chemical agent decreases. The total amount of chemical agent shall be controlled within 0.25 ~ 0.30 PV. The case calculation shows that hot water chemical flooding can expand the effective radius from 80 m to 400 m, more effectively use the reserves between injection and production wells, increase the oil recovery by 4.8 percentage points, and increase the oil yield by 31.7 m3/t per ton of agent. Discussion: It is suggested that Bohai B Oilfield can adopt hot water chemical flooding after the multiple thermal fluid huff and puff to continuously guarantee the oilfield production.